THE PROBLEMS OF AGREEMENT PROVISIONS IMPLEMENTATION BETWEEN UKRAINE AND THE EU: INFORMATION SUPPORT - К.І. К.І. Серебряк (Економіка та право)
In article the results of public opinion poll of the EU countries population are presented, their relationship to the process of expanding the Union is marked, the attitude of Ukrainians to Ukraine’s membership of the EU is defined. The problems and prospects of signing the Association Agreement between Ukraine and the European Union were considered. The article is based on the results of research conducted by the Razumkov Centre.